Position of Indians in other parts of the Empire - University of London School of Oriental and African Studies; Adam Matthew Digital; Imperial Conference ((1923, London, England)) (Adam Matthew Digital, 1923)
Part of Appendix V of the proceedings of the Imperial Conference, 1923. Contains addresses of: Secretary of State for India ; Sir Tej Bahadur Sapru ; Maharajah of Alwar ; Secretary of State for the Colonies ; Prime Minister of Canada ; Prime Minister of the Commonwealth of Australia ; Prime Minister of New Zealand ; Prime Minister of the Union of South Africa